Pathophysiological mechanisms in severe preeclampsia: role of upregulated proteins in blood pressure, extracellular matrix and immunity - Caroline Cristina Pinto-Souza; Julyane Natsumi Saito Kaihara; Bruno César Rossini; Ricardo de Carvalho Cavalli; Lucilene Delazari dos Santos; Valéria Cristina Sandrim (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: This study aims to compare the plasma protein profiles between 7 preeclampsia patients with severe features (PE+) and 7 preeclampsia patients without severe features (PE-) and 10 healthy pregnancies (HP); identify differentially expressed proteins among these groups and explore the altered signaling pathways and their association with the severity of this cardiovascular condition. Methods: Plasma proteins were quantified using mass spectrometry, followed by comprehensive bioinformatics and statistical analyses. Protein identification and annotation were performed using UniProt and PatternLab for Proteomics. Multivariate statistical analyses, including PLS-DA and sPLS-DA, as well as VIP score evaluation and Volcano plot visualization, were conducted with MetaboAnalyst to assess group separation and identify key discriminative features. Functional enrichment and pathway analyses were carried out using Metascape. Results: Using a fold change and volcano plot validation of 1.2, comparisons between HP and PE+ revealed that proteins such as AMBP (inter-alpha trypsin inhibitor light chain), VTN (vitronectin), CLU (clusterin), F2 (prothrombin), and PZP (pregnancy zone protein) were upregulated in PE+. Conversely, ITIH4 (inter-alpha trypsin inhibitor heavy chain H4), APOL1 (apolipoprotein 1) and SERPIND1 (heparin cofactor II) were downregulated in PE+ relative to HP. When comparing HP with PE-, SERPINA3 (alpha-1-antichymotrypsin) and HBB (hemoglobin subunit beta) were downregulated in PE-. Between PE- and PE+, APCS (serum amyloid P component) and HBB were upregulated in PE+; whereas SERPINC1 (antithrombin), PSG1 (pregnancy-specific beta-1-glycoprotein 1), ITIH4, and C5 (complement C5) were downregulated in PE+ compared to PE-. Conclusion: These findings offer valuable insights into the different pathophysiological mechanisms underlying the two subgroups of PE. The upregulated proteins in PE+ (AMBP, VTN, CLU, F2, PZP, APCS, and HBB) play key roles in regulating blood pressure, modulating the extracellular matrix and influencing immune responses. Overall, this research deepens our understanding of the complexity and clinical significance of PE.